Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 17041 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Salix herbacea L.", "HasCoordinate is true", { "or" : [ "BasisOfRecord is Fossil", "BasisOfRecord is Human Observation", "BasisOfRecord is Machine Observation", "BasisOfRecord is Observation", "BasisOfRecord is Literature Occurrence", "BasisOfRecord is Unknown evidence" ] } ] } The dataset includes 17041 records from 48 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0038991-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences